Jaminan Produk Halal bagi UMKM Terhadap Implementasi Program Sertifikat Halal Gratis Di Jawa Barat - Hadiyanto, Redi; Madjakusumah, Deden Gandana; Azis, Siti Fauziah; Firmansyah, Fahri Mulya; Ibadurrahman, Zayd (ITB AAS INDONESIA Surakarta, 2024)
Awareness of the importance of guaranteeing halal products is increasing among Indonesian people, especially in West Java. To meet this need, the government launched various initiatives, including the Free Halal Certificate Program (SEHATI) and the one million free certificates program by the Halal Product Guarantee Agency (BPJPH). This research aims to analyze the effectiveness of collaboration between the SEHATI and BPJPH programs in providing halal product guarantees as well as identifying the challenges and opportunities faced during implementation in West Java. This research uses a qualitative approach with data collection methods in the form of in-depth interviews, observation and document analysis. Informants consisted of small and medium entrepreneurs (UKM), representatives of BPJPH, the Institute for the Study of Food, Drugs and Cosmetics, the Indonesian Ulema Council (LPPOM MUI), as well as consumers in West Java. The research results show that the collaboration between the SEHATI program and BPJPH has significantly increased the number of halal certified products in West Java. This initiative has succeeded in making it easier for entrepreneurs, especially SMEs, to obtain halal certification at no cost, thus encouraging more halal products on the market. In addition, increased coordination and integration between BPJPH and the SEHATI program has helped reduce duplication of efforts and speed up the certification process. Research results show that although there are several challenges, collaboration between the SEHATI program and BPJPH in the one million free certificates program has had a significant positive impact on halal product guarantees in West Java. The recommendations put forward include increasing education and outreach about halal certification, simplifying bureaucratic procedures, as well as increasing technical and financial support for entrepreneurs.